Optical genome mapping - Anja Kovanda; Borut Peterlin (Medicina Fluminensis, 2026)
Optical genome mapping (OGM) is a novel method based on image acquisition of single, enzyme labelled, high-molecular-weight DNA molecules, that enables the detection of structural variants (SV). This includes copy neutral SV such as inversions, insertions and balanced translocations in size ranges that typically represent a challenge for sequence, array or PCR based methods, making the method applicative in the field of haematological and constitutional genetic testing alike. In constitutional setting, OGM is particularly useful for facioscapulohumeral dystrophy testing, validation of suspected variants from other technologies, as well as testing of rare-disease patients with previously negative genetic testing results.